Implementasi Kebijakan Program Pasar Pangan Segar Aman (Pas Aman) dalam Meningkatkan Keamanan Kualitas Pangan di Pasar Alai, Padang - Putri, Helena Yolanda; Yusran, Rahmadani (Journal of Civic Education, 2025)
This research examines the implementation of the Safe Fresh Food Market Program (PAS AMAN) policy as an effort to enhance food quality and safety at Alai Market in Padang Utara District, Padang City, while also identifying the key factors that support and hinder its execution. The PAS AMAN initiative is a government program designed to promote traditional markets that are clean, healthy, and capable of supplying fresh and safe food to consumers. Adopting a qualitative descriptive approach, this study gathered data through interviews, observations, and documentation involving the West Sumatra Provincial Food Agency, the Padang City Food and Health Offices, market authorities, and traders. The findings reveal that the implementation of PAS AMAN at Alai Market has progressed fairly well, supported by a strong legal foundation, effective coordination among institutions, and increased trader awareness regarding food safety. Nonetheless, several challenges persist, such as limited facilities, inadequate understanding among some traders, and long-standing practices that are difficult to change. Based on Van Meter and Van Horn’s policy implementation framework, the program’s effectiveness is determined by factors including the clarity of policy objectives, adequacy of resources, communication among implementing bodies, socio-economic conditions, and the attitudes of policy executors. Therefore, to maximize the program’s outcomes, continuous outreach, improved facilities, and sustained guidance are essential.